Origination : the geographies of brands and branding - Pike, Andy, 1968- (Chichester, West Sussex, UK : Wiley Blackwell, 2015)
'Andy Pike has given us a deeply researched and much needed analysis of the ways in which brands and branding are intertwined with space and place. Through a series of revelatory case studies of products and their places of origin, we learn how spatial context matters in the production of branded meaning and value. Origination will be an essential resource for scholars of branding, geography, cultural studies, and the contemporary global economy.' - Miriam Greenberg, Associate Professor of Sociology, University of California Santa Cruz, USA 'The symbolic landscape of late capitalism is cl.
The Geographies of Brands and Branding -- Origination -- 'Local' Origination... Newcastle Brown Ale -- 'National' Origination... Burberry -- 'Global' Origination... Apple -- Territorial Development.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed April 20, 2015).
Keywords: Commercial geography; Branding (Marketing); Brand name products; Branding (Marketing).; Globalization; Marketing; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Branding (Marketing); Commercial geography; Electronic books; Electronic books